Effectiveness of vestibular incision subperiosteal tunnel access technique in the treatment of multiple adjacent gingival recession defects: A systematic review - Prabhnoor Tuli; Abhay Pandurang Kolte; Rajashri Abhay Kolte; Vrushali Nilesh Lathiya (Journal of Indian Society of Periodontology)
Objective: To investigate the effectiveness of Vestibular Incision Subperiosteal Tunnel Access (VISTA) technique over other root coverage (RC) procedures for treating Millers Class I and II multiple adjacent gingival recession defects (MAGRD). Methods: Patient, Intervention, Comparison, and Outcome question was established, and a literature review was carried out across PubMed, Cochrane Libraries, EMBASE, and hand-searched journals till April 2023 to identify the clinical research on the effectiveness of the VISTA Technique for RC procedures. Only randomized controlled trials (RCTs) with a minimum of 6 months’ follow-up were considered. The outcomes assessed were complete RC (CRC), width of keratinized gingiva, and gingival thickness. Results: A total of 30 articles were retrieved and ultimately 7 RCTs that met the inclusion criteria were incorporated into the systematic review. VISTA with biomaterials showed significant improvements in all the treatment outcomes over other RC procedures. Specifically, VISTA + subepithelial connective tissue graft (CTG)/CTG achieved an average CRC of 93.95%, along with significant increase in other parameters. In addition, biomaterials such as platelet concentrates, collagen membrane, Bioguide enhanced GEM21S, and Acellular dermal matrix proved viable alternatives producing similar outcomes. Conclusion: VISTA technique is an effective procedure for treating MAGRD in terms of achieving CRC over other RC procedures. In addition, the use of biomaterials further enhances the treatment outcomes.